The „Mateusz” Readaptation Centre as a Response to Contemporary Trends in Polish Post-penitentiary Support System - Piątek, Krzysztof (Problemy społeczne: Trwałość i zmienność w dynamicznej rzeczywistości. Księga jubileuszowa z okazji 45-lecia pracy naukowej i dydaktycznej Profesor Jolanty Grotowskiej-Leder, 2022)
The study begins with presenting the interpretation doubts of the concept of post-penitentiary assistance, resulting from the fact of using it in various so-called social scientific disciplines, with particular conceptual confusion observed on the legal basis. In the following part, post-penitentiary aid in contemporary Poland is characterized, with particular emphasis on the institutional perspective. One of such institutions is the „Mateusz” Readaptation Center in Toruń, which is an example of the activity of a non-governmental organization in the field of post-penitentiary aid. The conclusion presents a methodological tool used mainly for the so-called action research, in the form of a social laboratory. The idea of conducting a social laboratory in the „Mateusz” center can be treated as one of the forms of testing new solutions to the problems of post-penitentiary aid in Poland.